A public health approach to promoting advance care planning to Aboriginal people in regional communities. (February 2014) - Sinclair, Craig; Williams, Glenda; Knight, Andrew; Auret, Kirsten
Abstract Objective To explore perceptions of Noongar community members towards advance care planning (ACP), while developing culturally appropriate information resources for use in community and hospital settings. Design Qualitative research methods, combining active health promotion with interviews and group discussions for participant feedback. Setting Six rural communities across the Great Southern region of Western Australia. Participants Eighteen Noongar community members consented to participate in interviews or group discussions. Interventions Community members received information about ACP at community events or home visits, from an Aboriginal health worker and palliative care researcher. Main outcome measures Semi‐structured interviews and group discussions were thematically analysed using a descriptive, exploratory approach. Research team reflections on community events also constituted data. Results Key themes impacting on perceptions of ACP included cultural approaches to dying, importance of family and kin, and appropriate communication. Participants were satisfied with the information resource and method of community engagement. Conclusions Culturally appropriate methods of engaging Aboriginal people in ACP discussions should include Aboriginal health workers and take a whole of community approach to awareness raising.